Evaluating the Surface Response of Discharge Events in a New Zealand Gulf-ROFI - Ø'Callaghan, Joanne M.; Stevens, Craig L. (Frontiers in Marine Science, 2017)
Using moorings with a surface expression, responses of buoyant river outflows were examined in the Firth-Hauraki Gulf system, New Zealand. The Firth region of freshwater influence (ROFI) behaves as a gulf-type ROFI where the balance of key processes lies between rotation and advection. The latter process is largely regulated by the frequency and amplitude of freshwater discharges. Using 12-months of observations from two inner Firth sites, the system was found to be salinity stratified for up to 4 months of a year. During the largest event (274 m3s-1, mean daily maximum) in 2012 near-oceanic surface salinity (34 psu) freshened substantially down to 28 psu over the upper 3 m. Time lags between freshwater inflows and ROFI response were 4 and 7 days at the Waiheke and WilsonB locations, respectively. Faster seaward advection of surface layers occurred for a minimum of 3 days and up to a week after peak discharges. High frequency winds (~ 3-hourly) were persistent in regulating surface flows over the annual cycle. Surface salinity had peaks in energy that were coherent with surface flows at periods of 16 to 32 days over the Austral winter. The duration of discharge events was O(days), yet responses by buoyancy and advection were evident for weeks to a month in the Firth ROFI.